Role of Computed Tomography In Evaluation of Patients With History of Chronic Headache - Rawal, Sanju; Mukhi, Sadhan; Subedi, Sandip; Maharjan, Surendra (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Headache is one of the universal experience and one of the most common symptom in medical practice. It is most frequently suffered illness by human beings. As much as 90 percent of individuals have at least one episode of headache each year and severe headache is reported to occur at least annually in 40 percent of the population. Population based estimates suggest that about 4 percent of adults have daily or near daily headache. Since majority of patients who present with chronic or recurrent headache have no significant intracranial abnormalities to be detected on neuroimaging. The main objective of our study was to obtain socio demographic status of patients presenting with history of chronic headache and to assess the role of CT scan in evaluation of such patients presenting to radiology department from various departments of Universal College of Medical Sciences & Teaching Hospital (UCMSTH). MATERIAL AND METHODS: All patients with complaints of chronic headache and referred to Department of Radiology from August 2013 to April 2014 were included in the study. Total of 193 cases were included. Intravenous contrast medium was given in all 193 cases. Patients were divided into two groups with normal and abnormal CT findings. Results were tabulated and analyzed for the diagnostic yield from imaging in evaluation of patient with history of chronic headache. RESULTS: Out of 193 patients, 182 had normal CT (94.31%) and 11(5.69%) had abnormal CT findings. Contrast enhanced CT scans did not improve lesion detection .Out of 11 abnormal CT findings 3 of them had intracranial space occupying lesion, 3 had calcified granuloma, 2 of them had sinusitis, 1 had hydrocephalus, 1 cerebral atrophy and 1 with persistent cavum septum pellucidum. CONCLUSION: The proportion of intracranial abnormalities detected by CT in patients with history of chronic headache in this study was similar to that of previous studies. This corroborates the evidence that the ability of CT scan in detecting intracranial pathology is low in patient with chronic headache with exclusion of any neurological abnormality.